Pregnancy and Vaginal Delivery after Sacrohysteropexy - Deniz Balsak; Ahmet Eser; Onur Erol; Derya Deniz Altıntaş; Şerif Aksin (Case Reports in Obstetrics and Gynecology)
Pregnancy and birth after a Pelvic Organ Prolapse (POP) surgery is a rare condition and less is known about the method for delivery. A 31-year-old women with gravida 3 para 3 underwent abdominal sacrohysteropexy and transobturatuar tape (TOT) procedures for stage III prolapse who delivered via vaginal birth and showed no relapse. Sacrohysteropexy is a good option for women with POP who desire fertility with a long term follow-up period.